THE USE OF DIEGETIC SOUNDS IN BUILDING A JUMP SCARE IN THE A QUIET PLACE (2018) MOVIE - Durotul Ngazizah (Language and Literature Faculty, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2021)
This research is conducted to analyze the diegetic sound and the components that built it played in the constructions of the jump scare in the A Quiet Place (2018) movie. There are two problem statements that the researcher formulated in this research, first what are the diegetic sound components that are part of the jump scare in the A Quiet Place (2018) movie? Second, how does the diegetic sound build jump scare in the A Quiet Place (2018) movie? The researcher used the qualitative method to examine the problem. The theory and approaches that the researcher used is Film Analysis, Diegetic Sounds, and Jump Scare. This study also includes the procedures of collecting data and procedure of analyzing data. The result of this study, first the diegetic sound indicated by the sound that came from the film's world shown by the situation by dominantly incorporating various natural or environmental diegetic sounds and using minimal dialogue in the A Quiet Place (2018) movie. Second, includes the roles of diegetic sounds in building jump scare in A Quiet Place (2018) movie.